Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.2147/jpr.s132485
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative sensory testing measures individual pain responses in emergency department patients

Abstract: BackgroundRefining and individualizing treatment of acute pain in the emergency department (ED) is a high priority, given that painful complaints are the most common reasons for ED visits. Few tools exist to objectively measure pain perception in the ED setting. We speculated that variation in perception of fixed painful stimuli would explain individual variation in reported pain and response to treatment among ED patients.Materials and methodsIn three studies, we 1) describe performance characteristics of bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Comparison of patient sex between the two treatment groups was performed using Fisher's exact test. To account for variation in sensitivity between individuals, 7,32,33 the 5 values for each test site, testing instrument, and test day were averaged. These averages were then subtracted from the patient's corresponding baseline (Day 0) values to establish changes from baseline for each patient.…”
Section: Methodsmentioning
confidence: 99%
“…Comparison of patient sex between the two treatment groups was performed using Fisher's exact test. To account for variation in sensitivity between individuals, 7,32,33 the 5 values for each test site, testing instrument, and test day were averaged. These averages were then subtracted from the patient's corresponding baseline (Day 0) values to establish changes from baseline for each patient.…”
Section: Methodsmentioning
confidence: 99%
“…While minimizing observer bias by testing hyperekplexia patients and healthy controls by different investigators, this might have introduced inter-observer variability to the quantitative sensory test measurements. However, several studies have consistently reported satisfactory to excellent inter-observer reliability of quantitative sensory test measures, when performed in a standardized setting by trained investigators (Geber et al, 2011;Nikolajsen et al, 2011;Dyck et al, 2014;O'Neill and O'Neill, 2015;Boland-Freitas et al, 2016;Duffy et al, 2017).…”
Section: Strength and Limitationsmentioning
confidence: 99%
“…Quantitative sensory testing is a validated experimental model of acute pain, and has been used in the development of novel analgesic agents 18 . Quantitative sensory testing includes standardized acute exposures to hot or cold temperatures as well as pressure algometry applied to the skin, and correlates with acute opioid pain relief achieved during clinical treatment in the emergency room 19 and post-operatively 20 . However, quantitative sensory testing has rarely been used to examine analgesic response in patients with opioid use disorder 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%